Multi-spacer typing as an effective method to distinguish the clonal lineage of Clostridium butyricum strains isolated from stool samples during a series of necrotizing enterocolitis cases. Issue 3 (March 2017) - Benamar, S.; Cassir, N.; Merhej, V.; Jardot, P.; Robert, C.; Raoult, D.; La Scola, B.
Summary: Background: Necrotizing enterocolitis (NEC) is a devastating gastrointestinal disease with high morbidity and mortality that predominantly affects preterm neonates during outbreaks. In a previous study, the present authors identified 15 Clostridium butyricum isolates from stool samples during a series of NEC cases involving four neonatal intensive care units. A clonal lineage of these strains was observed by in-silico multi-locus sequence typing. Aim: To confirm the previous findings by sequencing a larger number of C. butyricum genomes and using other genotyping approaches. Methods: The previously isolated 15 C. butyricum strains were characterized and compared with 17 other commensal and environmental C. butyricum strains using whole-genome sequencing (WGS). In addition, the clustering was analysed using multi-spacer sequence typing (MST). Findings: The core genome of C. butyricum was composed of 1251 genes, and its pan-genome consisted of 12, 628 genes with high variability between strains. It was possible to distinguish the clonal lineage of strains from a series of NEC cases, forming three clades with geographical clustering. The results obtained using WGS and MST approaches were congruent. Conclusion: MST is a fast, cheap and effective genotyping method for investigating NEC outbreaks associated with C. butyricum .